39=j+17

Simple and best practice solution for 39=j+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39=j+17 equation:



39=j+17
We move all terms to the left:
39-(j+17)=0
We get rid of parentheses
-j-17+39=0
We add all the numbers together, and all the variables
-1j+22=0
We move all terms containing j to the left, all other terms to the right
-j=-22
j=-22/-1
j=+22

See similar equations:

| 6n^2+2=-103 | | 2x-14.2=-6x+28 | | 3(5x-2)=15-2 | | 25n^2+1=2 | | 2x-9+2x-7=28 | | 3c=42-4c | | 20a=-140 | | 3m-8(-8m-2)=16-6m | | 5(2x+3)-4=3(2x+5) | | x^2-3=34 | | -6n-2n=16n= | | -66=6(x | | 9n^2+2=578 | | x-3=-1→x=20 | | -h/4=-4 | | -3+1.2=-3y+15-18 | | 5s=490 | | -6=r/8 | | 1/2x+x=180−x | | 2a+73=-4a+19 | | x+7=-9→x=16 | | 3n-I=8 | | 8n^2+5=21 | | -13z+(-3z)=32 | | 12x+x=180−x | | 783=27g | | 2x-16+9x=72 | | –9−8b=–7b | | 19=-24(4+z)-3 | | 3=-w/5 | | 2x^2-3x-22=x^2-12 | | 4x+x=74 |

Equations solver categories